Impact of artificial intelligence in business and society : opportunities and challenges /: opportunities and challenges. (2023) - La Torre, Davide; Appio, Francesco; Lazzeri, Francesca; Schiavone, Francesco; Masri, Hatem, 1964-
No abstract available